Rafting On The River - Briggs-Pattison, Sue And Harvey, Bev; Illustrated by Charles, Craig (New York Scholastic, 1998)
"Based on the lifestyle of the Yorta Yorta people of the Murray River, bear Barmah. ... Gives an insight into the lifestyles and experiences of the Koorie children who grew up this area."
Include Color Illustrations
Keywords: Reading (Primary)